Determinants of Independence in Exclusive Breastfeeding among Mothers with Diabetes Mellitus: A Cross-Sectional Study from Indonesia - Yulita, Emi; Ginting, Chrismis Novalinda; Chiuman, Linda; Erika, Erika (Journal of Current Health Sciences, 2025)
The global rise in diabetes mellitus (DM) among women of reproductive age poses significant challenges to achieving optimal exclusive breastfeeding (EBF) rates, especially in low- and middle-income countries such as Indonesia. This study aimed to examine the relationship between knowledge and experience of mothers with DM and their independence in providing EBF, addressing an urgent need for targeted intervention and policy support for this vulnerable population. An analytic observational study with a cross-sectional design was conducted at community health centers in Pekanbaru from June to November 2024, involving 98 breastfeeding mothers diagnosed with DM, recruited through convenience sampling. Structured questionnaires measured maternal knowledge, prior breastfeeding experience, and independence in EBF. The results showed that 57.1% of mothers had good knowledge and 53.1% had adequate breastfeeding experience, while 69.4% demonstrated independence in providing EBF. Bivariate analysis revealed significant relationships between knowledge and independence (p = 0.026) as well as experience and independence (p = 0.001). These findings underscore the importance of enhancing education and support for mothers with DM to improve EBF practices. It is recommended that healthcare policies and programs prioritize continuous, tailored education and counseling to empower mothers with DM and increase EBF coverage.